Hazret-Sultan historical-cultural be afraid museum (Journal of history, 2020)
The article discusses the museum of the country at the present stage, including historical, cultural, national history and the Kazakh people and other ethnic groups living in the country is rich in historical and cultural heritage is one of the natural open-air museums in promoting, preserving historical relics of the southern region and to promote the growing of Hazrat Sultan State historical and cultural Museum-reserve of history of the domestic stock systems, facilities, exhibits, etc. reported on numerous occasions. In addition, the museum of archeology and ethnology departments, especially in the museum, «GAR» The main exhibit room KA Yasawa underground layout of the room, «Qılwet» underground mosque KA Yasawa construction of the dome of the mosque on Friday that the family is considered to be a hammam. Article is about human’s family shows up material and spiritual culture which plays an important role in researches’ and museums’ advancement. Kazakhstan’s history museum and historyculture reservation in south region are closely related to studying of scientifical and historical preservation of South region’s legacy.Shows value of all historical materials, which are saved in Khazret Sultan’s museum. Key words: «Қyluet» museum exhibits, equipment, historical and cultural reserve, layout.